(untitled) - Jamil, Kaiser (Boca Raton, 1992)
This book provides a survey of biochemical, physiological and histological biomarkers of environmental stress, along with evaluations of the strengths and weaknesses of various techniques for different applications.
Đánh dấu sinh học trong cảnh báo ô nhiễm
Keywords: Indicators ( biology ),Biochemical markers,Environmental monitoring,Các chỉ số (sinh học),Dấu ấn sinh hóa,Kiểm soát môi trường